Characterizing the Epigenetic and Transcriptomic Responses to Perkinsus marinus Infection in the Eastern Oyster Crassostrea virginica - Johnson, Kevin M.; Sirovy, K. A.; Casas, Sandra M.; La Peyre, Jerome F.; Kelly, Morgan W. (Frontiers in Marine Science, 2020)
Eastern oyster populations in the northern Gulf of Mexico are routinely infected with the protistan parasite Perkinsus marinus, the cause of the disease commonly known as dermo. Recent experimental challenges among Atlantic coast populations have identified both resistant and susceptible genotypes using comparative transcriptomics. While controlled experimental challenges are essential first assessments, expanding this analysis to field reared individuals provides an opportunity to identify key genomic signatures of infection that appear both in the laboratory and in the field. In this study we combined reduced representation bisulfite sequencing with 3’ RNA sequencing (Tag-seq) to describe two molecular phenotypes associated with infection in oysters outplanted at a common garden field site. These combined approaches allowed us to examine changes in DNA methylation and gene expression for a large number of individuals (n=40) that developed infections during the course of a common garden outplant experiment. Our epigenetic analysis of DNA methylation identified significant changes in gene body methylation associated with increasing infection intensity, across genes associated with immune responses. There was a smaller transcriptomic response to increasing infection intensities with 32 genes showing differential expression, and 40 % of these genes were found to also be differentially methylated. While there was no clear pattern between direction of differential methylation and gene expression, there was a significant effect of percent methylation on gene-by-gene expression levels and the coefficient of variation in gene body methylation between treatments. These results show that heavily methylated genes have high levels of gene expression with low levels of variation. Comparing our differential expression results with previously published experimental P. marinus challenges identified overlapping expression patterns for genes associated with C1q-domain-containing and V-type proton ATPase proteins. Through our comparative transcriptomic approach using field reared individuals and co-expression network analysis we have also been able to identify a network of genes that change in expression in response to infection. These combined analyses provide evidence for a conserved response to P. marinus infections and suggest that gene body DNA methylation is a better predictor of gene expression variation than it is of the overall magnitude of gene expression.